Artificially sweetened beverages do not influence metabolic risk factors: a systematic review and meta-analysis - Qin, Lina; Yu, Yunfeng; Yu, Rong (Frontiers in Nutrition, 2025)
IntroductionThe influence of artificially sweetened beverages (ASBs) on metabolic risk factors for non-communicable diseases (NCDs) remains unclear. This study aimed to systematically review the literature concerning whether the effects of ASBs on body weight and metabolic risk factors are equivalent to those of unsweetened beverages (USBs).MethodsWe searched PubMed, Embase, Web of Science, and Cochrane Library databases from their establishment until March 3, 2025. Only randomized controlled trials (RCTs) comparing ASBs and USBs were included. Literature screening, data extraction, and bias evaluations were performed. Statistical analyses were performed using Review Manager 5.4 and Stata 15.0 software.ResultsNine RCTs involving 1,457 individuals were included. Meta-analysis findings indicated no statistically significant differences between ASB and USB groups in terms of weight, waist circumference, fasting blood glucose, glycated hemoglobin, homeostatic model assessment for insulin resistance, total cholesterol, triglycerides, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, systolic blood pressure, and diastolic blood pressure (all p > 0.05).ConclusionThe study findings do not support the hypothesis that ASBs pose significant risks or benefits in terms of metabolic risk factors for NCDs. However, given this study applied a heterogeneous ASB formula, it could not adequately consider the role of specific artificial sweeteners. Further research is needed to evaluate the potential effect of different artificial sweeteners and their doses on health.Systematic review registrationhttps://www.crd.york.ac.uk, identifier CRD420251027794.